2016
DOI: 10.13005/bbra/2052
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Educational Interventions based on the Continuous Care Model on the Quality of Life of Hemodialysis Patients

Abstract: End-stage renal disease (ESRD) is an irreversible clinical condition. These patients have many problems during treatment with dialysis such as physical, mental, and socioeconomic problem to assess the influence of educational interventions based on the continuous care model on the quality of life of hemodialysis patients. The present study is a controlled clinical trial .The study population consisted of the entire patients with advanced chronic kidney failure who were undergoing hemodialysis at hemodialysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Meanwhile, Haravi et al (2006) showed that group counseling led to a better body image among the breast cancer patients undergoing chemotherapy (14). Other studies on continuous care model, administrated by nurses, reported that it led to better sleep quality (10), quality of life (15,16), and reduction of stress, anxiety and depression (17) among patients. Rosenberg et al (2012) showed that patients' mean score of body image was significantly better in patients undergoing lumpectomy, compared to mastectomy (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Haravi et al (2006) showed that group counseling led to a better body image among the breast cancer patients undergoing chemotherapy (14). Other studies on continuous care model, administrated by nurses, reported that it led to better sleep quality (10), quality of life (15,16), and reduction of stress, anxiety and depression (17) among patients. Rosenberg et al (2012) showed that patients' mean score of body image was significantly better in patients undergoing lumpectomy, compared to mastectomy (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…Kualitas hidup menjadi ukuran yang sangat penting setelah pasien menjalani terapi pengganti ginjal seperti hemodialisa (Poorgholami, et al, 2016). Kualitas hidup diukur berdasarkan rasa subjektif dari kesejahteraan umum yang dirasakan oleh pasien yang juga akan digunakan sebagai ukuran klinis dalam hal perawatan medis pasien yang menjalani hemodialisis (Pakpour et al, 2010).…”
Section: Pendahuluanunclassified